RANCANG BANGUN MESIN PEMOTONG KENTANG BERBENTUK STICK - Saparin Saparin; Yudi Setiawan; Edi Irwan; Eka Sari Wijianti (Jurusan Teknik Mesin Fakultas Teknik Universitas Bangka Belitung, 2021)
This research is a design of a potato cutting machine. The ultimate goal of making the machine is the production of potato cubes. In planning the machine will be processed to produce stick-shaped potato pieces. The machine design is made with dimensions of 660 mm x 800 mm x 710 mm using an electric motor ½ Hp. The system of lowering the rotation uses a pully and belt 1: 2 and continued with a gearbox with a ratio of 1:40, the way the engine works is to rotate the crankshaft to move the piston / potato suppressor with a rotation of 17.5 Rpm. The study was conducted 3 times with 1000 grams of potatoes with an average yield of 702 grams of good cut, 27 grams unsuccessful, 271 grams behind. The production capacity of this stick-shaped potato cutting machine is capable of cutting as much as 20.29 kg / hour with a machine production efficiency of 70.02%.